First report of B chromosomes in three neotropical thorny catfishes (Siluriformes, Doradidae) - Takagui, Fábio Hiroshi (2017)
Fil: Takagui, Fábio Hiroshi. Universidad Estatal de Londrina. Centro de Ciencias Biológicas. Departamento de Biología General. Laboratorio de Citogenética Animal; Brasil.